Genetic polymorphisms of interleukin (IL)-1B, IL-1RN, IL-8, IL-10 and tumor necrosis factor α and risk of gastric cancer in a Chinese population - Wanli Lu; Kai‐Feng Pan; Lian Zhang; Dongxin Lin; Xiaoping Miao; Wei‐Cheng You (2004)
Helicobacter pylori infection and the cytokine-mediated inflammatory responses play important roles in gastric cancer pathogenesis. This case control study was conducted to assess the association between genetic polymorphisms in interleukin (IL)-1B, IL-1RN, IL-8, IL-10 and tumor necrosis factor alpha (TNFalpha), which are involved in H.pylori infection, and risk of gastric cancer. Genotypes were determined by PCR-based denaturing high-performance liquid chromatography analysis and direct DNA sequencing in 250 incident cases with gastric cancer and 300 controls recruited in Northern China. Serum levels of anti-H.pylori IgG and IgA were measured by enzyme-linked immunosorbent assay to indicate H.pylori infection. We found that the risk of gastric cancer was significantly elevated in subjects with the IL-8-251 AA [adjusted odds ratio (OR) 2.02; 95% confidence interval (CI) 1.27-3.21] or IL-10-1082 G (OR 2.02; 95% CI 1.24-3.29) or TNFalpha-308 AG (OR 1.81; 95% CI 1.04-3.14) genotype. An elevated risk of gastric cancer was observed in subjects with H.pylori infection and the IL-8-251 AA genotype (OR 2.54; 95% CI 1.38-4.72) or IL-10-1082 G carriers (OR 2.62; 95% CI 1.42-4.93). An increased OR was also suggested for IL-1B-31 and TNFalpha-238, but confidence intervals included the null value. There was no evidence of increased risk for any of the other polymorphisms evaluated. These findings suggest that genetic polymorphisms in IL-8, IL-10 and TNFalpha may play important roles in developing gastric cancer in the Chinese population.